Embodying the Sacred : Women Mystics in Seventeenth-Century Lima - Van Deusen, Nancy E. (Book collections on Project MUSE., 2017)
Through the lives of religious women in colonial Lima, a new understanding of the ways in which pious Catholic women engaged with material and immaterial notions of the sacred or were themselves objectified as conduits of the divine in spiritual narratives.